ANALISA KEKUATAN POROS KOMPOSIT POLYESTER SERAT BATANG PISANG YANG DISUSUN SIMETRI 25^0,45^0,65^0 TERHADAP PENGUJIAN PUNTIR - Cahyono, Trias Novan (2016)
The purpose of this study was to determine the strength of the banana stem fiber composite shaft with the polyester matrix to torsional test and observe macro photo torsional fracture after testing. The bark is peeled banana 1 m length of 4 layers of outer skin, continued pressing to crush the flesh of the banana skin to the fiber began to be seen. The process of taking fiber soaking in water for 1 month and then conducted taking fiber. Drying the fiber carried out at room temperature for 1 day. Furthermore, the process of alkalization with potassium permangate (KMnO4) 2% per 1 liter of distilled water in 2 hours soaking time. Drying is performed at room temperature followed the process in the oven at 35^0C for 1 hour so that the moisture content of 10%. Molding method (molding) is used to create a composite with the fiber direction of 25^0 / -25^0, 45^0 / -45^0 and 65^0 / -65^0 On torsional test, this test is used to describe the torsional strength and fracture shaft observe macro image of composite polyester fiber banana stems. The test results can be concluded phenomenon highest torsional strength test on the orientation angle 65^0, its torsional strength of 0.401 kg / mm^2. At the macro-structure of the composite specimen fracture suffered long fiber pull out due to the strength of the matrix decreases.